Persistent immune activation and altered gut integrity over time in a longitudinal study of Ugandan youth with perinatally acquired HIV - Dirajlal-Fargo, Sahera; Strah, Monika; Ailstock, Kate; Sattar, Abdus; Karungi, Christine; Nazzinda, Rashidah; Kityo, Cissy; Musiime, Victor; Funderburg, Nicholas; McComsey, Grace A. (Frontiers in Immunology, 2023)
Perinatally acquired HIV infection (PHIV) occurs during a critical window of immune development. We investigated changes in systemic inflammation and immune activation in adolescents with PHIV and those without HIV (HIV-) in Uganda. A prospective observational cohort study was performed in 2017-2021 in Uganda. All participants were between 10-18 years of age and without active co-infections. PHIVs were on ART with HIV-1 RNA level ≤400 copies/mL. We measured plasma and cellular markers of monocyte activation, T-cell activation (expression of CD38 and HLA-DR on CD4+ and CD8+), oxidized LDL, markers of gut integrity and fungal translocation. Groups were compared using Wilcoxon rank sum tests. Changes from baseline were examined with 97.5% confidence intervals on relative fold change. P values were adjusted for false discovery rate. We enrolled 101 PHIV and 96 HIV-; among these, 89 PHIV and 79 HIV- also had measurements at 96 weeks. At baseline, median (Q1, Q3) age was 13 yrs (11,15), and 52% were females. In PHIV, median CD4+ cell counts were 988 cells/µL (638, 1308), ART duration was 10 yrs (8, 11), and 85% had viral load <50 copies/mL throughout the study, 53% of participants had a regimen switch between visits, 85% of whom switched to 3TC, TDF and DTG. Over 96 weeks, while hsCRP decreased by 40% in PHIV (p=0.12), I-FABP and BDG both increased by 19 and 38% respectively (p=0.08 and ≤0.01) and did not change in HIV- (p≥0.33). At baseline, PHIVs had higher monocyte activation (sCD14) (p=0.01) and elevated frequencies of non-classical monocytes (p<0.01) compared to HIV- which remained stable over time in PHIV but increased by 34% and 80% respectively in HIV-. At both time points, PHIVs had higher T cell activation (p≤0.03: CD4+/ CD8+ T cells expressing HLA-DR and CD38). Only in PHIV, at both timepoints, oxidized LDL was inversely associated with activated T cells(p<0.01). Ugandan PHIV with viral suppression have some improvement in markers of inflammation over time, however T-cell activation remains elevated. Gut integrity and translocation worsened only in PHIV over time. A deeper understanding of the mechanisms causing immune activation in ART treated African PHIV is crucial.